Low dosage of rimonabant leads to anxiolytic-like behavior via inhibiting expression levels and G-protein activity of kappa opioid receptors in a cannabinoid receptor independent manner. (February 2015) - Zádor, Ferenc; Lénárt, Nikolett; Csibrány, Balázs; Sántha, Miklós; Molnár, Máté; Tuka, Bernadett; Samavati, Reza; Klivényi, Péter; Vécsei, László; Marton, Annamária; Vizler, Csaba; Nagy, György M.; et al.
Abstract: What is known: There is an increasing number of studies demonstrating the direct effect of the cannabinoid receptor 1 (CB1 ) antagonist/inverse agonist rimonabant on the opioid system. The kappa opioid receptors (KORs) are well known to mediate depression- and anxiety-like behavior. Clinical studies on chronic rimonabant administration have revealed that rimonabant leads to a very similar pathophysiology, suggesting a potential impact of rimonabant on KORs. Objectives: Our objectives were to examine the putative effects of rimonabant on KOR ligand binding, G-protein activity, protein expression and how all these contribute to the development of depression- and anxiety-like behavior. Results: In Chinese hamster ovary (CHO) cell membranes transfected with rat KOR (CHO-rKOR) rimonabant inhibited KOR agonist [ 3 H]U69593 binding in the micromolar range in competition binding experiments and specifically reduced KOR basal activity at lower micromolar concentrations in [ 35 S]GTPγS binding assays. Rimonabant significantly inhibited dynorphin (1–11)-induced [ 35 S]GTPγS binding in micromolar range in CHO-rKOR cells, CB1 knockout (CB1 K.O.) and CB1 /CB2 double knockout mouse forebrain membranes. A single dose of i.p. 0.1 mg/kg rimonabant significantly reduced dynorphin (1–11)-induced KOR G-protein activity and KOR protein expression levels 24 h following the administration in both wild type and CB1 K.O. mice forebrain. Furthermore, in elevated plus maze mice showed an anxiolytic-like effect upon rimonabant injection that could be reversed by 1 mg/kg KOR antagonist norbinaltorphimine. The anxiolytic-like effects were further confirmed with the light–dark box test. Conclusion: Rimonabant reduced KOR ligand binding, receptor mediated G-protein activity and protein expression level, which overall leads to altered anxiety-like behavior. Highlights: We investigate the effect of rimonabant on kappa opioid receptor (KOR) function. Rimonabant in vitro inhibits KOR binding, basal activity and G-protein activity. Rimonabant in vivo inhibits KOR G-protein activity and protein expression. The effects are cannabinoid receptor 1 independent. Rimonabant shows KOR mediated anxiolytic-like effect in mouse.